Stability of alkylation and sulphonation units joint work in alkylbenzene sulphuric acid manufacturing; Petroleum and Coal; Vol. 58, iss. 2 - Dolganova I. O. Irena Olegovna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Vasyuchka K. A. Kseniya Anatoljevna (2016, 2016)
Title screen